2019
DOI: 10.1021/acs.cgd.8b01794
|View full text |Cite
|
Sign up to set email alerts
|

Correlations of Crystal Structure and Solubility in Organic Salts: The Case of the Antiplasmodial Drug Piperaquine

Abstract: Five organic salts of the antiplasmodial drug piperaquine (PQ, C 29 H 32 Cl 2 N 6 ) were synthesized and characterized by X-ray diffraction methods. The corresponding solubilities in water and acetic acid solutions were evaluated in the 20−50 °C (293−323 K) T range by UV−vis spectroscopy, with the aim of elucidating how they depend on chemical, structural, and thermodynamic factors. Experiments were complemented by DFT calculations, both in vacuo and in the solid state, to estimate changes in thermodynamic sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 60 publications
(100 reference statements)
0
19
0
Order By: Relevance
“…The last significant feature appreciable from Figure 2 is a large blue leaf at d i + d e ≈ 3.8 Å, roughly halfway the main diagonal, which signals π• • • π interactions. These are due to extended stacking arrangements of the quinoline rings, which all lie roughly orthogonal to the [10 1] direction (Figure 2a), along which they form parallel displaced ladders similar to those observed in other quinoline [10,11] and aromatic compounds [40]. Inversion-related organic moieties are stacked in a perfectly parallel fashion (Supplementary Materials, Section S2), but whenever symmetry-independent rings are close to each other, a slanted arrangement is preferred [40], with quinoline least-squares planes displaying an offset angle of 12.60(2) • with respect to each other.…”
Section: Crystal Packingmentioning
confidence: 58%
See 1 more Smart Citation
“…The last significant feature appreciable from Figure 2 is a large blue leaf at d i + d e ≈ 3.8 Å, roughly halfway the main diagonal, which signals π• • • π interactions. These are due to extended stacking arrangements of the quinoline rings, which all lie roughly orthogonal to the [10 1] direction (Figure 2a), along which they form parallel displaced ladders similar to those observed in other quinoline [10,11] and aromatic compounds [40]. Inversion-related organic moieties are stacked in a perfectly parallel fashion (Supplementary Materials, Section S2), but whenever symmetry-independent rings are close to each other, a slanted arrangement is preferred [40], with quinoline least-squares planes displaying an offset angle of 12.60(2) • with respect to each other.…”
Section: Crystal Packingmentioning
confidence: 58%
“…This kind of analysis definitely suggests the existence of a very rich territory of yet unexplored chemistry. For some years now, we have been studying the reactivity of transition metals with quinoline-based antimalarial drugs in order to understand their mechanism of action at the molecular level [9][10][11]. Quinoline compounds can actively enter the metabolism by binding specific metal targets, including late transition elements like copper and zinc [12].…”
Section: Introductionmentioning
confidence: 99%
“…A search of literature references could not find any physicochemical or structural properties that reliably predicted the solubility on a diverse group of molecular salts. Although discrete trends were sometimes extracted from salts of the same compound series, exceptions and outliers were rather abundant. ,,, …”
Section: Resultsmentioning
confidence: 99%
“…In addition, the dissolution of an API is closely related to its Gibbs free energy of solvation (Δ G * solv ), and a larger Δ G * solv usually results in poor solubility. , Δ G * solv values of PUEM and PUE-Na in different media are shown in Table S8. It was found that the values of Δ G * solv for PUEM were 18.81, 18.61, and 17.54 kJ/mol in pH 1.2 HCl, water, and pH 6.8 PBS, respectively.…”
Section: Discussionmentioning
confidence: 99%